2022
DOI: 10.3390/jof8080882
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Integrated with Metabolomics: Assessing the Central Metabolism of Different Cells after Cell Differentiation in Aureobasidium pullulans NG

Abstract: When organisms are stimulated by external stresses, oxidative stress is induced, resulting in the production of large amounts of reactive oxygen species (ROS) that inhibit cell growth and accelerate cellular aging until death. Understanding the molecular mechanisms of abiotic stress is important to enhance cellular resistance, and Aureobasidium pullulans, a highly resistant yeast-like fungus, can use cellular differentiation to resist environmental stress. Here, swollen cells (SCs) from two different different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous studies suggested that yeast-like cells can differentiate into swollen cells via the regulation of low pH values (<6.0) [ 22 ]. Figure 5 shows that the hyper-osmotic stress and low pH values (ultimately 3.57) ( Table S3 ) under the OC prompted the cells of strain ZH27 to form swollen cells earlier and more extensively than those under the IC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies suggested that yeast-like cells can differentiate into swollen cells via the regulation of low pH values (<6.0) [ 22 ]. Figure 5 shows that the hyper-osmotic stress and low pH values (ultimately 3.57) ( Table S3 ) under the OC prompted the cells of strain ZH27 to form swollen cells earlier and more extensively than those under the IC.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, most of the swollen cells under the OC contained 1-2 large vacuoles but the swollen cells with one vacuole were dominant after 48 h, whereas swollen cells under the IC had one large vacuole and several small ones (Figure 5). Previous studies suggested that yeast-like cells can differentiate into swollen cells via the regulation of low pH values (<6.0) [22]. Figure 5 shows that the hyper-osmotic stress and low pH values (ultimately 3.57) (Table S3) under the OC prompted the cells of strain ZH27 to form swollen cells earlier and more extensively than those under the IC.…”
Section: Dynamic Changes In Cell Morphology During Batch Fermentationmentioning
confidence: 85%
See 3 more Smart Citations